Flow structures in evolving scour holes caused by 2-D plunging jets and wall jets - Si, Jinhua (2019)
The present study used Particle Image Velocimetry (PIV) to measure the flow structures in evolving scour holes caused by two types of 2-D jet: a 2-D plunging jet downstream of a weir and a 2-D wall jet beneath a sluice gate with an apron. Probably for the first time, the interesting jet-flipping phenomenon has been observed in a local scour hole caused by a 2-D plunging jet in the presence of an apron, and PIV effectively measure the dramatically dynamic flow structures of the cyclic jet-flipping in the scour holes. The results clearly depict a complex dynamic roller system consisting of four rollers involved in the development of local scour holes. The average kinetic energy (AKE) distributions reveal that the rollers are maintained by jet impingement on both the concave scoured bed and the water surface. Moreover, the self-similarity of flow fields within the local scour hole is also examined.